Ventricular stabilization with a customized decellularized cardiac ECM-based scaffold after myocardial infarction alters gene expression in a rodent LAD-ligation model - Aubin, Hug; Rath, Lenard; Vey, Alexandra; Schmidt, Vera; Barth, Mareike; Weber, Elvira; Lichtenberg, Artur; Akhyari, Payam (Frontiers in Bioengineering and Biotechnology, 2022)
Objectives: Decellularized extracellular matrix (dECM) is increasingly used in a wide range of regenerative medicine applications and may also offer the potential to support injured myocardium. Here, we evaluated the myocardial gene expression pattern after myocardial infarction (MI) in a standardized rodent LAD-ligation model with and without ventricular stabilization with a customized, cardiac dECM-based scaffold (cdECM). Methods: MI was induced in male Wistar rats by standard LAD-ligation and confirmed 14 days post-intervention by echocardiographic parameters (FAS<40%). Cardiac ECM from donor rats was used to generate individual cdECM-scaffolds (tissue engineered myocardial sleeve, TEMS), which were epicardially implanted after confirmed MI for ventricular stabilization. After 4 and 8 weeks heart function was assessed by echocardiography, rats were sacrificed and explanted hearts were analyzed. In addition to histological analysis, standardized anterior left ventricular wall myocardial tissue samples were assessed by quantitative real-time PCR evaluating the specific gene expression pattern for immunomodulatory (IL-10, TGFBR2, TNFα), pro-angiogenic (VEGFA, FGF2, PGF, PDGFB), pro-survival (HGF, SDF1, IGF1, AKT1), remodeling-associated (TIMP1, MMP2, MMP9) and infarction-specific (NPPA, NPPB) markers. Results: Ventricular stabilization led to integration of the TEMS-scaffold into the myocardial scar with varying degrees of cellular infiltration, as well as significantly improved echocardiographic parameters demonstrating attenuation of maladaptive cardiac remodeling. Further, TEMS implantation after MI altered the myocardial gene expression pattern. Differences in gene expression were most striking after 4 weeks with significantly reduced expression of NPPA (0.36±0.26 vs. 0.75±0.40; p<0.05), NPPB (0.47±0.25 vs. 0.91±0.429; p<0.01), TGFBR2 (0.68±0.16 vs. 0.90±0.14; p<0.01) and PDGFB (0.81±0.13 vs. 1.06±0.14; p<0.01) as well as increased expression of IL-10 (5.93±5.67 vs. 1.38±0.60; p<0.05), PGF (1.48±0.38 vs. 1.09±0.25; p<0.05) and IGF1 (1.67±0.70 vs. 1.03±0.42; p<0.05). However, after 8 weeks differences in the gene expression patterns of remodeling-associated, and pro-angiogenic markers could still be observed between groups. Conclusion: Ventricular stabilization via TEMS implantation after MI did not only led to biological integration of the cdECM-scaffolds into the host tissue and improved functional cardiac parameters, but also altered 4 and 8 week gene expression of infarcted myocardium, possibly contributing to reducing chronic deteriorating effects while increasing the potential for myocardial regeneration.